Electric field tuned MoS2/metal interface for hydrogen evolution catalyst from first-principles investigations. (15th December 2017) - Ling, F L; Zhou, T W; Liu, X Q; Kang, W; Zeng, W; Zhang, Y X; Fang, L; Lu, Y; Zhou, M
Abstract: Understanding the interfacial properties of catalyst/substrate is crucial for the design of high-performance catalyst for important chemical reactions. Recent years have witnessed a surge of research in utilizing MoS2 as a promising electro-catalyst for hydrogen production, and field effect has been employed to enhance the activity (Wang et al 2017 Adv. Mater. 29, 1604464; Yan et al 2017 Nano Lett. 17, 4109–15). However, the underlying atomic mechanism remains unclear. In this paper, by using the prototype MoS2 /Au system as a probe, we investigate effects of external electric field on the interfacial electronic structures via density functional theory (DFT) based first-principles calculations. Our results reveal that although there is no covalent interaction between MoS2 overlayer and Au substrate, an applied electric field efficiently adjusts the charge transfer between MoS2 and Au, leading to tunable Schottky barrier type (n-type to p-type) and decrease of barrier height to facilitate charge injection. Furthermore, we predict that the adsorption energy of atomic hydrogen on MoS2 /Au to be readily controlled by electric field to a broad range within a modest magnitude of field, which may benefit the performance enhancement of hydrogen evolution reaction. Our DFT results provide valuable insight into the experimental observations and pave the way for future understanding and control of catalysts in practice, such as those with vacancies, defects, edge states or synthesized nanostructures.